MSR SPLAT, A Language Analysis Toolkit - Quirk, Chris; Choudhury, Pallavi; Gao, Jianfeng; Suzuki, Hisami; Toutanova, Kristina; Gamon, Michael; Yih, Scott Wen-tau; Vanderwende, Lucy; Cherry, Colin (Proceedings of NAACL-HLT 2012, 2012)
We describe MSR SPLAT, a toolkit for language analysis that allows easy access to the linguistic analysis tools produced by the NLP group at Microsoft Research. The tools include both traditional linguistic analysis tools such as part-of-speech taggers, constituency and dependency parsers, and more recent developments such as sentiment detection and linguistically valid morphology. As we expand the tools we develop for our own research, the set of tools available in MSR SPLAT will be extended. The toolkit is accessible as a web service, which can be used from a broad set of programming languages.